2020
DOI: 10.1101/2020.05.02.072439
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Release of potential pro-inflammatory peptides from SARS-CoV-2 spike glycoproteins in neutrophil-extracellular traps

Abstract: COVID-2019 has progressed in around 10-15% of patients to an acute respiratory distress syndrome characterized by extensive pulmonary inflammation and elevated production of pro-inflammatory cytokines. Neutrophil activation seems to be crucial in the initiation and perpetuation of this exacerbated lung inflammation. However, the precise mechanisms by which this activation occurs remain yet elusive. To this end, this in silico study tried to identify potential proinflammatory inducing peptides (PIPs) produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A higher number of blood neutrophils (also called neutrophilia) contributes to the initiation and progression of pulmonary inflammation in later stages. In relation to SARS-COV-2, Blanco-Miguez et al, have identified 9 potential proinflammatory inducing peptides (PIPS) that may be linked to an increase in host inflammation [26].…”
Section: Stage 1: Early Stage Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher number of blood neutrophils (also called neutrophilia) contributes to the initiation and progression of pulmonary inflammation in later stages. In relation to SARS-COV-2, Blanco-Miguez et al, have identified 9 potential proinflammatory inducing peptides (PIPS) that may be linked to an increase in host inflammation [26].…”
Section: Stage 1: Early Stage Of Infectionmentioning
confidence: 99%
“…In response to SARS-CoV-2, neutrophils release inflammatory peptides, suggesting their association with the pulmonary strike [26]. Neutrophils accumulate early at the site of inflammation followed by a sustained population of monocytes, macrophages, and lymphocytes.…”
Section: Stage 1: Early Stage Of Infectionmentioning
confidence: 99%